1992
DOI: 10.1021/jm00082a012
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazines as lipid peroxidation inhibitors and cytoprotective agents

Abstract: A series of phenothiazines was synthesized and evaluated as in vitro inhibitors of iron-dependent lipid peroxidation. The MIC (minimum tested concentration that gave greater than or equal to 50% inhibition) for 2-(10H-phenothiazin-2-yloxy)-N,N-dimethylethanolamine methanesulfonate (6) was 0.26 microM. Whereas methyl substitution at N-10 diminished activity nearly 100-fold, other structural modifications such as varying the amine group, the distance separating the amine substituent from the phenothiazine nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…It has already been shown that positively charged ammonium groups impede antioxidant action in derivatives of phenothiazine (Yu et al, 1992); nevertheless lipophilicity has to be considered with care, as far as drug design is concerned. Neuroprotective agents should be able to penetrate the blood-brain barrier effectively, but very lipophilic compounds with long alkyl chain membrane anchors are usually excluded from passively entering the brain (Seelig et al, 1994;Moosmann and Behl, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that positively charged ammonium groups impede antioxidant action in derivatives of phenothiazine (Yu et al, 1992); nevertheless lipophilicity has to be considered with care, as far as drug design is concerned. Neuroprotective agents should be able to penetrate the blood-brain barrier effectively, but very lipophilic compounds with long alkyl chain membrane anchors are usually excluded from passively entering the brain (Seelig et al, 1994;Moosmann and Behl, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…The primary mechanism responsible for the cerebroprotective effect is unclear at the present time because multiple factors may influence the cascade of events leading to postischemic brain damage. However, the in vitro profile of 2-(10//-phenothiazin-2-yloxy)-AT,JV-dimethylethanamine hydrochloride 12 supports the possibility that antioxidant mechanisms may underly its ability to ameliorate brain damage when administered before and after a transient ischemic insult. Our study is therefore consistent with the hypothesis that oxidantmediated lipid peroxidation may be involved in the pathophysiology of postischemic brain injury.…”
Section: -(10h-phenothiazin-2-yloxy)-nn-dimethylethanamine Hydrochlomentioning
confidence: 99%
“…Using a whole cell assay, we evaluated representative examples from that study as cytoprotective agents and found that they protected primary cultures of rat hippocampal neurons from hydrogen peroxide-induced toxicity. 12 Under these conditions, chlorpromazine was ineffective, which suggests that antioxidant capacity and in vitro cytoprotective efficacy may be related for this class of compounds.…”
Section: See Editorial Comment P 1291mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the phenothiazine structure, mainly represented by chlorpromazine, is considered to possess antioxidant properties [15][16][17][18][19], only few reports have studied the antioxidant activity of other phenothiazine derivatives [20,21]. Due to structural similarities as well as taking into consideration the involvement of reactive oxygen species (ROS) in pathological conditions such as inflammation, degenerative diseases, and aging, we considered it of interest to further investigate our newly synthesized 2,7-diazaphenothiazine derivatives for antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%